The analogy of law in civil law educational practice - Mikryukov, Viktor (2020)
The objective of this research was to show how actively the legal analogy mechanism is applied in current civil law practice, identifying the reasons for the main role of legal analogy as an active tool in the justice administration process. The method of analogy was considered as the key tool of the object of the study, and together with the special comparative legal and technical instruments, the author applied general logical methods that are characteristic of the most civilized studies, such as analysis and synthesis, induction and deduction, comparison and generalization. Furthermore, the author defined some important cases that were decided by applying legal analogies and may form the basis for future investigations in the development of relevant judicial practice. In this sense, the author's contribution consists of a new concept of the correlation between the development and breakdown of legal standards and the degree of demand for legal analogy in jurisprudence.